Integration of plasmonic Au nanoparticles in TiO2 hierarchical structures in a single-step pulsed laser co-deposition. (15th October 2018) - Bricchi, Beatrice Roberta; Ghidelli, Matteo; Mascaretti, Luca; Zapelli, Andrea; Russo, Valeria; Casari, Carlo Spartaco; Terraneo, Giancarlo; Alessandri, Ivano; Ducati, Caterina; Li Bassi, Andrea
Abstract: The plasmonic resonance of noble metal nanoparticles (NPs) can be exploited to enhance the photoresponse of wide band gap oxides in view of several solar energy applications. Here, we demonstrate single-step synthesis of plasmonic Au nanoparticles integrated in TiO2 hierarchical nanoporous layers through a vapor phase pulsed laser co-deposition approach. Specifically, we report the fabrication and characterization of Au NPs-decorated TiO2 forest-like systems with tunable porosity and density as well as the morphological/structural evolution as a function of Au content and we discuss the corresponding optical properties. The effect of post-deposition thermal treatment has been investigated as well in order to control TiO2 crystallization and Au NPs nucleation and growth. Optical analyses show the onset of characteristic plasmonic resonance of Au NPs with the increase of film absorption in the visible range. Preliminary tests of photodegradation of methyl orange dye indicate that the integration of Au NPs leads to a significant increase of the catalytic activity of nanoporous TiO2 . Our results suggest the potentiality of this approach for the synthesis and the integration of metallic NPs within wide band gap semiconductors, while paving the way toward novel plasmonic-based devices. Graphical abstract: Highlights: Plasmonic Au nanoparticles (NPs) have been integrated in nanostructured TiO2 films by single step pulsed laser co-deposition. The plasmonic properties of Au-TiO2 films are affected by the deposition conditions, the Au at.% and annealing treatments. Au NPs are homogenously distributed within TiO2 . Annealing treatments favor NPs growth, inducing TiO2 crystallization. Au NPs increase light absorption of the TiO2 film in the visible region showing a localized surface plasmon resonance peak. Photodegradation tests show that the presence of Au NPs in TiO2 films significantly increases the catalytic action.